Nuclear factor-κB activation is not involved in a MPTP model of Parkinson's disease - Teismann, Peter; Schwaninger, Markus; Weih, Falk; Ferger, Boris (Neuroreport, 2001)
In the present study the involvement of hydroxyl free radicals and nuclear factor-κB (NF-κB) activation was investigated in the MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) model of Parkinson's disease. MPTP (30 mg/kg, s.c.) produced a significant 2-fold increase in hydroxyl free radicals in the striatum of C57BL/6 mice determined by microdialysis in combination with the salicylate hydroxylation assay. Electrophoretic mobility shift assays did not detect NF-κB activation after MPTP treatment. Furthermore, p50-deficient mice showed only minor differences in striatal dopamine and metabolite levels as well as tyrosine hydroxylase immunoreactivity after MPTP administration in comparison to wildtype mice. We postulate that, although hydroxyl radical production was enhanced, NF-κB plays only a minor role in the MPTP model because neither neurochemical nor immunocytochemical parameters were altered in p50-deficient mice in comparison to controls.
Gesehen am 01.04.2021